Multiple pigmentations in Laugier‐Hunziker‐Baran syndrome. Issue 2 (29th November 2019) - Yamamoto, Jun‐Ichiro; Kasamatsu, Atsushi; Higo, Morihiro; Endo‐Sakamoto, Yosuke; Ogawara, Katsunori; Sunohara, Masataka; Shiiba, Masashi; Uzawa, Katsuhiro; Tanzawa, Hideki
Abstract: Laugier‐Hunziker‐Baran (LHB) syndrome is an acquired, macular hyperpigmentation of the lips, and oral mucosa, often associated with pigmentation of the nails, palms, and fingertips. LHB syndrome is considered to be a benign disease with no systemic manifestation or malignant potential. Normally, no treatment is required for this condition, unless for esthetic reason, mainly due to pigmentation on the lip mucosa. Here we present a case of LHB syndrome, 32‐year‐old male, whose pigmentations on his tongue, buccal mucosa, palate, and ventral surface of fingertip, diagnosed by clinical and dermoscopic findings.